Types of absence from work and wages of young workers with apprenticeship training - Kunze, Astrid [Verfasser] (My University, 2017)
"This paper explores the short-and long-term effects on wages of absence from work for young highly attached skilled male and female workers in West Germany. The analysis distinguishes different types of career absence: unemployment, maternity leave for female workers, compulsory service for male workers and other non-work spells. We find negative effects for all types of work absence, except for compulsory service for men. Compulsory service has a positive short-term wage effect. Unemployment decreases wages in the short term only, and for women more strongly than for men. Maternity leave leads to substantial losses for women. An important finding of this study is that maternity leave leads to substantially higher wage losses than other types of work absence, especially in the long term." (Author's abstract, BIBB-Doku)
Keywords: G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 2.4.5 Gender Mainstreaming; Erwerbstätiger; Ausbildungsabsolvent; Lohnhöhe; Einflussfaktor; Fehlzeiten; Arbeitslosigkeit; Mutterschutz; Wehrdienst; Geschlechterdifferenz